The Symbolic Meaning of Traditional Cuisine in the Mongaruwa Tradition among the Gorontalo Community - Rahmawati Latama; Harto S. Malik; Rahman Taufiqrianto Dako (Transbahasa, 2026)
This study aims to explore and describe the symbolic meanings of traditional cuisine in the Mongaruwa tradition among the Gorontalo community. A qualitative approach with a descriptive design was employed to gain an in-depth understanding of cultural practices embedded in traditional food. Data were collected through literature review, cultural observation, and documentation of several traditional foods, including Bajoe, Tiliaya, Nasi Kuning, Bilindi, Lutu, and Watingo. The data were analyzed using thematic analysis to identify recurring patterns and underlying meanings. The findings reveal that traditional foods in the Mongaruwa tradition embody important cultural values such as togetherness, gratitude, prosperity, and respect for guests and family. Each type of food carries symbolic meanings that reflect the social and cultural norms of the Gorontalo community. Furthermore, the tradition shows how traditional cuisine functions as a medium for preserving and transmitting local wisdom across generations. In conclusion, traditional cuisine in the Mongaruwa tradition not only serves a consumptive purpose but also represents a meaningful cultural expression that supports identity and continuity.